Effects of high levels of glucose on the steroidogenesis and the expression of adiponectin receptors in rat ovarian cells - Ramé Christelle; Tosca Lucie; JeanPierre Eric; Chabrolle Christine; Dupont Joëlle (BMC, 2008)
Abstract Background Reproductive dysfunction in the diabetic female rat is associated with altered folliculogenesis and steroidogenesis. However, the molecular mechanisms involved in the reduction of steroid production have not been described. Adiponectin is an adipocytokine that has insulin-sensitizing actions including stimulation of glucose uptake in muscle and suppression of glucose production in liver. Adiponectin acts via two receptor isoforms - AdipoR1 and AdipoR2 - that are regulated by hyperglycaemia and hyperinsulinaemia in liver and muscle. We have recently identified AdipoR1 and AdipoR2 in rat ovary. However, their regulation in ovaries of diabetic female rat remains to be elucidated. Methods We incubated rat primary granulosa cells in vitro with high concentrations of glucose (5 or 10 g/l) + or - FSH (10-8 M) or IGF-1 (10-8 M), and we studied the ovaries of streptozotocin-induced diabetic rats (STZ) in vivo. The levels of oestradiol and progesterone in culture medium and serum were measured by RIA. We used immunoblotting to assay key steroidogenesis factors (3beta HSD, p450scc, p450 aromatase, StAR), and adiponectin receptors and various elements of signalling pathways (MAPK ERK1/2 and AMPK) in vivo and in vitro. We also determined cell proliferation by [3H] thymidine incorporation. Results Glucose (5 or 10 g/l) impaired the in vitro production in rat granulosa cells of both progesterone and oestradiol in the basal state and in response to FSH and IGF-1 without affecting cell proliferation and viability. This was associated with substantial reductions in the amounts of 3beta HSD, p450scc, p450 aromatase and StAR proteins and MAPK ERK1/2 phosphorylation. In contrast, glucose did not affect the abundance of AdipoR1 or AdipoR2 proteins. In vivo, as expected, STZ treatment of rats caused hyperglycaemia and insulin, adiponectin and resistin deficiencies. Plasma progesterone and oestradiol levels were also reduced in STZ rats. However, the amounts of 3beta HSD and p450 aromatase were the same in STZ rat ovary and controls, and the amounts of StAR and p450scc were higher. Streptozotocin treatment did not affect adiponectin receptors in rat ovary but it increased AMPK phosphorylation without affecting MAPK ERK1/2 phosphorylation. Conclusion High levels of glucose decrease progesterone and oestradiol production in primary rat granulosa cells and in STZ-treated rats. However, the mechanism that leads to reduced ovarian steroid production seems to be different. Furthermore, adiponectin receptors in ovarian cells are not regulated by glucose.